The Impact of Perceptions of Positive COVID-19 Information on Travel Motivation and Intention: Evidence From Chinese University Students - Li, Shanshan; Liu, Chenyu; Wu, Zhusheng; Ma, Ying; Chen, Baoxia; Gao, Shiying; Chen, Zichao; Xin, Shuang (Frontiers in Psychology, 2022)
The COVID-19 pandemic has influenced the tourism industry in various ways, including tourists’ travel motivations and intentions. Unlike previous studies that have focused on the dark side of the pandemic, this study adds the dimension of perceptions of positive information on COVID-19 to the Theory of Planned Behavior to explore their influence on travel motivation and intention. 470 valid questionnaires were collected from a sample of Chinese university students. The results showed that the students’ perceptions of positive COVID-19 information positively impacted their travel intentions through the variables of perceived behavioral control, travel attitudes, and travel motivations. Perceived behavioral control was the mediating variable that most explained the impact of perceptions of positive COVID-19 information on travel motivation and intention. This study contributes to the understanding of the influence of the COVID-19 pandemic on tourism and of university students’ travel motivations and intentions. It also offers implications for the tourism industry to formulate relevant recovery strategies during and after the pandemic.